Opportunities and Challenges in Global Quantification of RNA-Protein Interaction via UV Cross-Linking - Vieira-Vieira, Carlos H.; Selbach, Matthias (Frontiers in Molecular Biosciences, 2021)
RNA-binding proteins (RBPs) are key mediators of posttranscriptional gene expression control. However, the links between cell signalling on the one hand and RBP function on the other are understudied. While thousands of posttranslational modification (PTM) sites on RBPs have been identified, their functional roles are only poorly characterized. RNA-interactome capture (RIC) and cross-linking immunoprecipitation (CLIP) are attractive methods that provide information about RBP-RNA interactions on a genome-wide scale. Both approaches rely on the in situ UV cross-linking of RBPs and RNAs, biochemical enrichment and analysis by RNA-sequencing (CLIP) or mass spectrometry (RIC). In principle, RIC- and CLIP-like methods could be used to globally quantify RBP-RNA interactions in response to perturbations. However, several biases have to be taken into account to avoid misinterpretation of the results obtained. Here, we focus on RIC-like methods and discuss four key aspects relevant for quantitative interpretation 1) the RNA isolation efficiency; 2) the inefficient and highly variable UV cross-linking, 3) the baseline RNA occupancy of RBPs, and 4) indirect factors affecting RBP-RNA interaction. We highlight these points by presenting selected examples of PTMs that might induce differential quantification in RIC-like experiments without necessarily affecting RNA-binding. We conclude that quantifying RBP-RNA interactions via RIC or CLIP-like methods should not be regarded as an end in itself but rather as starting points for deeper analysis.